(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Tourism covers all areas necessary for such activities. Provides their relationship. It brings humanity closer to nature, contributes to the further social and economic development of society in exchange for the correct and necessary use of it in the process of studying nature. Natural tourism is called ecotourism, which serves to preserve and increase the number of unique objects (rocks, rock formations, nature reserves, natural reservoirs and national parks) formed by nature under the influence of the sun, rain and wind.